Die verandering van 'n territoriale verpleegdiensontwerp na 'n matriksverpleegdiensontwerp - M.C. Herselman; M.E. Muller; M.C. van Huyssteen (AOSIS, 1991)
In this study two decentralised organisational designs in nursing management were investigated The purpose of the study was to investigate the effect of two different designs, namely the territorial and matrix designs, on the attitudes and perceptions of nurses towards their work. An explorative descriptive multi-phase study was conducted. The attitudes and perceptions of nurses were assessed by means of the Michigan Organisational Assessment Scale, during the territorial design and after changing to a matrix design. An analysis of the data showed a positive and statistically significant change in attitudes and perceptions in the matrix design, and therefore the directional hypothesis was accepted. Recommendations include further refinement of the matrix design, as well as training and accompaniment of nurse managers to implement the principles.